2007
DOI: 10.1108/13552550710759997
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Chinese entrepreneurial motivation

Abstract: Purpose -Debates in the literature on entrepreneurship concentrate on whether the focus should be on psychological variables or the external environment. Despite most studies being on the former, many others argue that the external environment is more useful in understanding business start-ups. This paper seeks to examine the relative influence of both types of variables. Design/methodology/approach -Data were collected from 337 Chinese respondents in three different groups: first, people who do not want to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(89 citation statements)
references
References 38 publications
4
85
0
Order By: Relevance
“…Sandhu and colleagues (2011) found that financing, access to markets, government support and availability of information are critical resources that can impact the success of start-ups. Personal factors, such as aversion to risk, fear of failure and aversion to stress and hard work are also common barriers faced by aspiring entrepreneurs (Taormina & Lao, 2007;Wang & Wong, 2004). In fact a "fear of failure" has been cited as the top reason given worldwide for not starting a business (Sandhu et al, 2011).…”
Section: Entrepreneurial Intention and Female Entrepreneurshipmentioning
confidence: 99%
“…Sandhu and colleagues (2011) found that financing, access to markets, government support and availability of information are critical resources that can impact the success of start-ups. Personal factors, such as aversion to risk, fear of failure and aversion to stress and hard work are also common barriers faced by aspiring entrepreneurs (Taormina & Lao, 2007;Wang & Wong, 2004). In fact a "fear of failure" has been cited as the top reason given worldwide for not starting a business (Sandhu et al, 2011).…”
Section: Entrepreneurial Intention and Female Entrepreneurshipmentioning
confidence: 99%
“…Some authors defined success from tangible (objective) points of view such as revenue or a firm's growth, personal wealth creation, profitability, turnover (Perren, 2000;Amrit et al 2000). Other studies (Watson et al 1998;Taormina and Lao, 2007) associated entrepreneurial success with continued business operations, operating for at least three years. Some other studies have interpreted the success from intangible points of view where intangible assets (e.g., goodwill of firm) are linked to key factors of success.…”
Section: Business Success Of Entrepreneurmentioning
confidence: 99%
“…Watson, Horgarth-Scott and Wilson, (1998) and Dafna (2008) evaluated the success of the business through its ability to continue to carry out its trading activities. In addition, there are some researchers who measure the success of the business based on its ability to operate more than three years (Vesper, 1990;Watson et al, 1998;Taormina & Lao, 2007). In addition, business success is also measured by the profitability of the acquired business and the average level of profit compared to the industry whether lower, equal to or higher than the average level of industry profits (Abdul Manaf, Omar & Yee, 2012).…”
Section: Business Successmentioning
confidence: 99%